2018
DOI: 10.1104/pp.18.00028
|View full text |Cite
|
Sign up to set email alerts
|

The Potato MAP3K StVIK Is Required for the Phytophthora infestans RXLR Effector Pi17316 to Promote Disease

Abstract: Plant pathogens deliver effectors to manipulate processes in their hosts, creating a suitable environment for invasion and proliferation. Yet, little is known about the host proteins that are targeted by effectors from filamentous pathogens. Here, we show that stable transgenic expression in potato () and transient expression in of the arginine-any amino acid-leucine-arginine effector Pi17316 enhances leaf colonization by the late blight pathogen Expression of Pi17316 also attenuates cell death triggered by th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
54
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 56 publications
(54 citation statements)
references
References 78 publications
0
54
0
Order By: Relevance
“…Recognition of the oomycete elicitin INF1, leading to localized cell death, can be used as a readout for successful immune signaling (Kamoun et al, 1997;Du et al, 2015). PiAVR2 has been shown previously to suppress INF1-triggered cell death (ICD; Turnbull et al, 2017), as do several other characterized P. infestans effectors, such as PiAVR3a, Pi18215, Pi02860, and Pi17316 (Bos et al, 2010;Zheng et al, 2014;Yang et al, 2016;He et al, 2018b;Murphy et al, 2018). Transient coexpression of INF1 with full-length and truncated forms of PiAVR2 was used to assess the extent of immune suppression.…”
Section: Interaction With the Bsl Family Is Essential For Piavr2 Virumentioning
confidence: 99%
See 1 more Smart Citation
“…Recognition of the oomycete elicitin INF1, leading to localized cell death, can be used as a readout for successful immune signaling (Kamoun et al, 1997;Du et al, 2015). PiAVR2 has been shown previously to suppress INF1-triggered cell death (ICD; Turnbull et al, 2017), as do several other characterized P. infestans effectors, such as PiAVR3a, Pi18215, Pi02860, and Pi17316 (Bos et al, 2010;Zheng et al, 2014;Yang et al, 2016;He et al, 2018b;Murphy et al, 2018). Transient coexpression of INF1 with full-length and truncated forms of PiAVR2 was used to assess the extent of immune suppression.…”
Section: Interaction With the Bsl Family Is Essential For Piavr2 Virumentioning
confidence: 99%
“…The late blight pathogen Phytophthora infestans has been shown to use both strategies to achieve virulence (Whisson et al, 2016). Whereas the RXLR (Arg2any amino acid2Leu2Arg motif) effectors AVIRULENCE 3a (AVR3a), PITG_11383 (PexRD2), PITG_03192 (Pi03192), and SUPPRESSOR OF EARLY FLG22-INDUCED IMMUNE RESPONSE 3 (SFI3) reduce defenses by means of interaction with positive regulators of immunity (Bos et al, 2010;Gilroy et al, 2011b;McLellan et al, 2013;King et al, 2014;He et al, 2018a), recent research has shown that RXLR effectors Pi04089, Pi04314, Pi02860, and Pi17316 interact with negative regulators of immunity (Wang et al, 2015;Boevink et al, 2016a;Yang et al, 2016;He et al, 2018b;Murphy et al, 2018). These effector targets are capable of attenuating P. infestans infection when silenced, increasing Phytophyhora infection colonization when overexpressed, or both, classifying them as "susceptibility (S) factors" in late blight infection (van Schie and Takken, 2014;Boevink et al, 2016b;Whisson et al, 2016).…”
mentioning
confidence: 99%
“…Nevertheless, type III effectors from bacterial plant pathogens, such as HopAI1 from P. syringae, which targets MPK3 and MPK6, can also directly inactivate MAPK cascade components that positively regulate immunity. Moreover, the P. syringae effector AvrB targets MPK4 to promote its activity as a negative regulator of immunity (Cui et al, 2010), and the P. infestans effector Pi17316 targets the susceptibility factor VASCULAR HIGHWAY1interacting kinase (VIK), also to exploit its role as a negative immune regulator (Murphy et al, 2018). Thus bacterial and oomycete effectors directly target both positive and negative regulators of immunity within MAPK cascades.…”
Section: Stmap3kb2 Acts In Parallel With Stmap3k« In Cf4/avr4 Inductimentioning
confidence: 99%
“…The effector Pi11383/ PexRD2 specifically targets the kinase domain (KD) of MAP3K«, directly inhibiting its activity to perturb plant defense responses (King et al, 2014). Recently, Murphy et al (2018) reported that the effector Pi17316 interacts with the host MAP3K, StVIK, which acts as a susceptibility factor to enhance P. infestans colonization.…”
mentioning
confidence: 99%
“…Notably, suppression of host immunity seems to be a major function of most effectors, as was demonstrated in the model plant Nicotiana benthamiana by monitoring their ability to suppress elicitor‐triggered cell death or to enhance pathogen leaf colonisation and in the bacteria Pseudomonas syringae by assessing their ability to promote pathogen pathogenicity (Fabro et al ., ; Liu et al ., ; Wang et al ., , ; Xiang et al ., ). RXLR effectors target diverse pathways within the host cell to suppress plant immunity, such as preventing secretion of defence‐related proteases (Bozkurt et al ., ), reducing the accumulation of reactive oxygen species around invasion sites (Dong et al ., ), perturbing mitogen‐activated protein kinase (MAPK) pathways (King et al ., ), supporting or promoting the activity of negative immune regulators (Boevink et al ., ; Murphy et al ., ), suppressing RNA silencing and reducing accumulation of small RNAs (Qiao et al ., , ), and reprograming pre‐mRNA splicing (Huang et al ., ). Although accumulating evidence shows that pathogenic bacteria and fungi deploy effectors to manipulate phytohormone pathways to defeat immunity (Kazan and Lyons, ; Ma and Ma, ), a few RXLR effectors were identified to connect to hormone signalling pathways.…”
Section: Introductionmentioning
confidence: 99%